Respuesta :
(f of g)(x)=f(g(x))
(f of g)(-7)=f(g(-7))
find g(-7) first for easier time
g(-7)=2(-7)-6=-14-6=-20
f(g(-7))=f(-20)
f(-20)=-3(-20)-4=60-4=56
(f of g)(-7)=56
(f of g)(-7)=f(g(-7))
find g(-7) first for easier time
g(-7)=2(-7)-6=-14-6=-20
f(g(-7))=f(-20)
f(-20)=-3(-20)-4=60-4=56
(f of g)(-7)=56
In order to do this, we must first find g(-7). By plugging -7 into the equation for g, we get g(-7) = -20. Next, we must plug this value into the equation for f(-20). This then gives us a final answer of (f of g)(-7) = 56.
Hope this helps!
Hope this helps!